Effects of increasing temperature on predator-prey interaction between beetle larvae and tadpoles. (2nd September 2019) - de Mira-Mendes, Caio Vinícius; Costa, Renan Nunes; Dias, Iuri Ribeiro; Carilo Filho, Leildo Machado; Mariano, Rodolfo; Le Pendu, Yvonnick; Solé, Mirco
ABSTRACT: In the present study we used larval amphibians ( Rhinella jimi ) as prey, and beetle larvae ( Hydrophilus sp.) as predator to assess if increased water temperature influences predator-prey dynamics. The experiment was carried out in replicated aquatic microcosms with two different water temperatures (control and a 'warming water' scenario). Survival of tadpoles decreased significantly in the treatment compared to the control and at the end of the experiment, all tadpoles in the 'warming water' scenario had been ingested, unlike in the control treatment, where only half of the tadpoles were ingested. Our results demonstrate that the alterations in abiotic conditions (water temperature) can reshape predator-prey dynamics in a future scenario of global warming. The consequent increase of predation may intensify negative effects on population size in anuran larvae. Although changes are likely, they are complex and often counterintuitive.